2017
DOI: 10.17533/udea.rccp.v30n3a02
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic tools used in the evaluation of the canine spleen: A review

Abstract: Herramientas ultrasonográfi cas usadas en la evaluación del bazo en caninos: Revisión de literaturaFerramentas ultrassonográfi cas para avaliação do baço em cães: Revisão da literatura AbstractThe spleen is one of the most susceptible organs to primary tumours, metastasis, and a wide range of diseases of the hematopoietic system. Therefore, detailed assessment of the spleen is of great importance in veterinary medicine, especially in dogs, due to their economic and sentimental value, and as an experimental mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…While it reaches 16±0.1cm in Bengal fox (Firdous and Maya 2013). Regarding the dog, the average splenic length is highly variable according to the different breeds (Maronezi et al 2017). Moreover, this study revealed that the thickness of the red fox's spleen is 0.4-0.5cm at the apex and 0.5-0.6cm at the base.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…While it reaches 16±0.1cm in Bengal fox (Firdous and Maya 2013). Regarding the dog, the average splenic length is highly variable according to the different breeds (Maronezi et al 2017). Moreover, this study revealed that the thickness of the red fox's spleen is 0.4-0.5cm at the apex and 0.5-0.6cm at the base.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, this study revealed that the thickness of the red fox's spleen is 0.4-0.5cm at the apex and 0.5-0.6cm at the base. While in a dog, the maximum thickness of the normal spleen is 1.7cm (Maronezi et al 2017).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Its portability and easy manipulation also make it easily available for both pet owners and veterinarians [ 37 , 38 , 39 , 40 , 41 ]. When compared to other diagnostic imaging techniques, CEUS also holds several advantages: it is painless, non-toxic, and radiation-free [ 1 , 2 , 14 , 29 ], and it has been described as widely available, easy-to-use, and less expensive than other imaging methods [ 29 ]. It also provides a clear picture of organs that are more difficult to observe on a survey radiograph and B-mode ultrasound, and abdominal CEUS can eliminate the need for other tests such a CT or an MRI [ 18 , 19 , 24 , 37 , 38 , 39 , 40 , 41 ].…”
Section: Ceus Applied For Dogs and Catsmentioning
confidence: 99%
“…CEUS has been shown to be a particularly valuable tool for splenic analysis, with the ability to determine and monitor alterations in the size, presence, and character of focal lesions, as well as detect specific alterations in its normal vascular pattern [ 14 , 15 , 16 , 17 ]. Indeed, in the last 20 years, the use of CEUS techniques for the examination of the spleen in humans has been increasingly pursued and several guidelines [ 16 ] and specific studies have arisen [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%